Studies of low-energy K− hadronic interactions with light nuclei by AMADEUS. (April 2020) - Del Grande, R; Bazzi, M; Bragadireanu, A M; Bosnar, D; Cargnelli, M; Clozza, A; Curceanu, C; De Paolis, L; Fabbietti, L; Ghio, F; Guaraldo, C; Iliescu, M; et al.
Abstract: The AMADEUS collaboration aims to provide precise experimental information on the K − strong interaction with nucleons in the low-energy regime. The step 0 of AMADEUS consists in the re-analysis of the data collected with the KLOE detector at the DAΦNE collider during the 2004/2005 data taking campaign. The absorptions of low-momentum K − s in the nuclei contained in the detector and the beam pipe setup (H, 4 He, 9 Be and 12 C) are investigated. Information on the K − single and multi-nucleon interactions are extracted from the study of the Λ π − and p correlated production in the final state.